Interferon for hepatitis B: US experience. - Perrillo, R P (1993)
This paper reviews the results of recent studies carried out in the USA on the treatment of chronic hepatitis B with interferon alfa-2b. In the US multicentre trial, 37% of patients lost hepatitis B e antigen (HBeAg) and hepatitis B virus (HBV)-DNA when treated with 5 million units (MU) daily for 16 weeks, compared to 42% in the US National Institutes of Health (NIH) trial treated with 10 MU thrice weekly for 16 weeks. In both studies, the loss of HBeAg and HBV-DNA was associated with virological, biochemical, histological, and clinical improvement. Long term follow up in the National Institutes of Health study showed that 65% of responders had disappearance of HBsAg over a mean of four years, suggesting that termination of the HBV carrier state may be possible.